A Sediment Magnetic Record in the North Pacific Across the Mid-Pleistocene Transition and its Implication on Asian Dust Evolution - Shin, Ji Young; Hyeong, Kiseong; Kim, Wonnyon (Frontiers in Earth Science, 2021)
Eolian dust deposited in the North Pacific is an important archive of evolutionary history of Asia interior source regions. Here we present a ~1 Myr sedimentary magnetic record from the central North Pacific, to characterize eolian dust property since the middle Pleistocene. For the studied sediments, magnetic components are identified mainly as biogenic magnetite and detrital magnetic minerals (dust and volcanic origins), based on coercivity analysis, microscopic observations, and sedimentological information. The detrital magnetic component is characterized by high coercivity (>100 mT) and shows a long-term increase in concentration since ~1 Ma. In particular, the concentration shows a considerable increase at ~0.8–0.7 Ma compared to inorganic silicate fraction, indicative of magnetic mineral enrichment in detrital sediment fraction. At the same time, coercivity distribution of the detrital component also decreases, which can be attributed to an increase in ferrimagnetic mineral contribution. As the detrital sediments are primarily wind-blown particles, such ferrimagnetic enrichment implies a change of dust source materials after ~0.8 Ma, which could be explained by reorganization of atmospheric circulation and/or regional aridification in source regions across the Mid-Pleistocene Transition. The dust property change in source areas is likely synchronized across the North Pacific, based on the similarity of the long-term trend of magnetic signals.